Flow and heat transfer in a nanofluid thin film over an unsteady stretching sheet - R.C. Aziz,; I. Hashim,; Abbasbandy, S. (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study analyzes the heat transfer of a thin film flow on an unsteady stretching sheet in nanofluids. Three different types of nanoparticles are considered; copper Cu, alumina Al2O3 and titania TiO2 with water as the base fluid. The governing equations are simplified using similarity transformations. The resulting coupled nonlinear differential equations are solved by the Homotopy Analysis Method (HAM). The analytical series solutions are presented and the numerical results obtained are tabulated. In particular, it shows that the heat transfer rate decreases when nanoparticles volume fraction increases.